The Monitoring Effect of More Frequent Disclosure - Downar, Benedikt; Ernstberger, Jürgen; Link, Benedikt (Contemporary Accounting Research, 2018)
ABSTRACT This paper examines the monitoring effect of disclosure frequency from a shareholder perspective. For our analyses, we use a setting in the European Union in which reporting frequency requirements differed across and within countries before being harmonized by a directive requiring the implementation of quarterly disclosure. We investigate how both cross‐sectional differences in reporting frequency and their harmonization affect shareholders' ability to monitor managers. To gauge monitoring effects, we use shareholders' valuation of cash assets. We find that semi‐annual reporters exhibit lower cash valuation than quarterly reporters. Using a difference‐in‐differences approach, we show that these differences recede after semi‐annual reporters implement a higher reporting frequency. Our results are consistent with the notion that more frequent disclosure reduces expected agency costs by providing shareholders with the opportunity for timelier monitoring to constrain managers from expropriating corporate resources. In additional analyses, we find that this monitoring effect is robust to using alternative measures of the change in cash and agency costs as well as alternative benchmark groups. Further, we find stronger effects when corporate governance or earnings quality is low.